Combining Strategic Management with Knowledge Management: Trends and International Perspectives - Ioannis, Rossidis; Belias, Dimitrios (International Review of Management and Marketing, 2020)
Knowledge management has emerged as a key lever for improving performance, boosting productivity and creativity and facilitating innovation in organizational settings. Knowledge Management is a modern multidisciplinary process of exploiting knowledge and information of an organization in order to achieve organizational objectives. The particular nature of knowledge management is proving to be a very useful tool in the field of strategic management providing valuable knowledge and information enforcing strategic planning. The aim of this paper is to analyze the interdependency between strategic management and knowledge management. By outlining the main strategic management perspectives in contemporary business literature and combining them with current knowledge management perspectives, an indication of the evolution of research pertaining to strategic knowledge management emerges. The article focuses on the synergies of knowledge-related capabilities in explaining the formation of strategic aspects. Keywords: Strategic Management, Knowledge Management, Global Environment JEL Classifications: D8, L1, M1, M16 DOI: https://doi.org/10.32479/irmm.9621